2017
DOI: 10.1109/mcom.2017.1601065
|View full text |Cite
|
Sign up to set email alerts
|

Non-Orthogonal Multiple Access in Multi-Cell Networks: Theory, Performance, and Practical Challenges

Abstract: Non-orthogonal multiple access (NOMA) is a potential enabler for the development of 5G and beyond wireless networks. By allowing multiple users to share the same time and frequency, NOMA can scale up the number of served users, increase the spectral efficiency, and improve user-fairness compared to existing orthogonal multiple access (OMA) techniques. While single-cell NOMA has drawn significant attention recently, much less attention has been given to multi-cell NOMA. This article discusses the opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
256
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(258 citation statements)
references
References 12 publications
1
256
0
1
Order By: Relevance
“…Furthermore, in order to increase the attainable performance of the SIC receiver, cooperative NOMA transmission has been proposed in [29] [30]. A range of investigations related to multi-cell NOMA schemes were carried out in [31]- [33]. Moreover, since having an increased number of cell-edge users typically degrades the efficiency of coordinated multi-point (CoMP) transmissions, this limitation was circumvented by a promising NOMA solution proposed for a CoMP system in [34].…”
Section: A Power-domain Nomamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in order to increase the attainable performance of the SIC receiver, cooperative NOMA transmission has been proposed in [29] [30]. A range of investigations related to multi-cell NOMA schemes were carried out in [31]- [33]. Moreover, since having an increased number of cell-edge users typically degrades the efficiency of coordinated multi-point (CoMP) transmissions, this limitation was circumvented by a promising NOMA solution proposed for a CoMP system in [34].…”
Section: A Power-domain Nomamentioning
confidence: 99%
“…It has been shown that the average rate coverage of a NOMA cluster is better than that of its counterpart OMA cluster for higher number of users per cell and for higher target rate requirements. Furthermore, an up-todate literature review of interference management techniques that apply NOMA in multi-cell networks has been provided in [33], including both NOMA using joint processing and NOMA relying on coordinated scheduling/beamforming. The major practical issues and challenges that arise in the implementation of multi-cell NOMA have also been highlighted in [33], such as the SIC implementation issues, imperfect CSI, as well as multi-user power allocation and clustering.…”
Section: A Power-domain Nomamentioning
confidence: 99%
“…The major design target of NOMA is to introduce controllable mutual interference among users to achieve a fine tradeoff between multiplexing gain and detection reliability. According to both theoretical and numerical analysis, NOMA outperforms OMA with respect to SE, EE, and connectivity [8][9][10][11]. To grasp the development of NOMA technologies, some published review papers have presented different aspects of NOMA.…”
Section: Section 4 Section 5 Section 3 Sectionmentioning
confidence: 99%
“…Furthermore, NOMA can be jointly designed with cooperative multiple point (CoMP) [9,109,110] or multipleantenna technology [41,[111][112][113]. Also, there have been some initial studies about employing NOMA in wireless power transfer network to increase the access opportunities [114][115][116].…”
Section: Joint Design With Othermentioning
confidence: 99%
“…NOMA is also helpful in a multi-cell environment to manage inter-cell interference [6]. To deal with practical constraints such as receiver complexity, it has been proposed in [7] to perform the uplink multi-user detection needed in NOMA over several smaller subsets of users, while each subset transmits on a different channel.…”
Section: B Related Workmentioning
confidence: 99%